MANAJEMEN PROGRAM LAYANAN BIMBINGAN KONSELING - david hidayat (UNISAN JURNAL, 2024)
Abstract Etymologically guidance counseling comes from the word "Guidance" which comes from the verb "to guide" which means to show, guide, lead or help, so guidance can generally be interpreted as assistance or guidance. According to the term guidance, it is a process of helping individuals through their own efforts to determine and develop their abilities in order to obtain personal happiness and social benefits. Of course, the guidance and counseling program is because the influence of the media is so prominent in the lives of students. Guidance Counseling Teachers try to provide all efforts that can continue to be used to shape students’ bad morals in two ways, namely in the classroom and outside the classroom, in the classroom by using advice methods, exemplary methods, punishment methods (not physical punishment but more directed towards spiritual Keywords: Management, Guidance Counseling